Media Manipulation as a Tool of Information Warfare: Typology Signs, Language Markers, Fact Checking Methods - Konstankevych, Iryna; Kostusiak, Nataliia; Shulska, Nataliia; Stanislav, Olga; Yelova, Tetiana; Kauza, Iryna (My University, 2022)
The article analyzes the manipulations that exist in the Ukrainian media space due to Russian propaganda in the conditions of the information war. Harmful information material was collected through a comprehensive survey of social networks. Its dissemination aims to create panic among the Ukrainian population, discrediting the authorities, the military, and the army, threatening the loss of the country's independence and democracy, etc. Based on the study of manipulative communication technologies used by the Russian mass media in wartime, it was revealed that effective methods are the use of mediators, information blockade, rewriting of history, the technique of shifting accents, sensationalism, and psychological shock. A common method of manipulation in the Russian Federation is the creation of virtual reality through myths and the construction of various images, stamps, and simulacra. Typical signs of hostile media manipulations are singled out: appeal to emotions; questionable sources of origin of the information or their absence; misrepresentation of facts; expressive hyperbolization or surrealism, and others. Evidence of manipulative news is the low language culture of this kind of message: the absence of elementary spelling rules, violations of linguistic and stylistic norms, the use of Russianisms or other lexical inaccuracies, and factual and logical errors. Effective fact-checking methods are proposed for detecting and refuting various types of disinformation.
Keywords: Fact-checking; Fake; Information war; Linguistic communicative markers; Media manipulation; Russian propaganda